Pengaruh Kualitas Pelayanan Terhadap Kepuasan Penumpang Pada PT Dharma Lautan Utama - Rezky Nurbakti; Sulawati Sulawati (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The purpose of this study was to determine the effect of the quality of service on KM Ships. Dharma Rucitra 7 has a partial and simultaneous effect on passenger satisfaction at PT. Dharma Lautan Utama Makassar branch on the KM Ship. Dharma Kencana 7. The analytical methods used in this research are observation, interviews, questionnaires, documentation, and library research. Determination of the sample was determined by sampling saturation (census) and obtained as many as 60 respondents. The results showed that (1) Partially, Product Quality affects Purchasing Decisions at PT. Dharma Lautan Utama Parepare Branch. This is evidenced by the results of testing the hypothesis t test where, t count > t table (2.283 > 2.004) and significant < 0.05 (0.026 > 0.05). Partially, the price affects the purchasing decision at the office of PT. Dharma Lautan Utama Parepare Branch. This is indicated by the results of testing the hypothesis t test where t count < t table (3.764 > 2.004) and is significant > 0.05 (0.000 <0.05). While partially, Trust has an effect on Purchasing Decisions at the Office of PT. Dharma Lautan Utama Parepare Branch. This is indicated by the results of testing the hypothesis t test where, t count < t table (2.586 > 2.004) and not significant > 0.05 (0.012 <0.05), (2) Simultaneously Product Quality, Price and Trust affect Decision Purchasing at PT. Dharma Lautan Utama Parepare Branch. This is shown by the results of testing the hypothesis test f, where f count > f table (206.033 > 2.37) and significantly < 0.05 (0.000 < 0.05), (3) The results of the coefficient of determination of 0.917 indicate Product Quality as an independent variable affect the dependent variable, namely 91.7%.